Упростите выражение ( а- в) ( а + в) - ( а - в)^2 / ав- в^2

0 голосов
28 просмотров

Упростите выражение ( а- в) ( а + в) - ( а - в)^2 / ав- в^2


Алгебра (23 баллов) | 28 просмотров
Дано ответов: 2
0 голосов
Правильный ответ

Решите задачу:

\frac{(a-b)(a+b)-(a-b)^{2}}{ab-b^{2}}= \frac{a^{2}-b^{2}-a^{2}+2ab-b^{2}}{b(a-b)}= \frac{2ab-2b^{2}}{b(a-b)}=\frac{2b(a-b)}{b(a-b)}=2
(63.8k баллов)
0 голосов

Решите задачу:

\frac{(a-b)(a+b)-(a-b)^2}{ab-b^2}=\frac{(a-b)(a+b-a+b)}{b(a-b)}=\\\\=\frac{(a-b)*2b}{b(a-b)}=2
(237k баллов)